EGCG Promotes Neurite Outgrowth through the Integrin β1/FAK/p38 Signaling Pathway after Subarachnoid Hemorrhage. (25th January 2021) - Zhang, Yuyuan; Han, Mengguo; Sun, Xiaoxue; Gao, Guojun; Yu, Guoying; Huang, Liong; Chen, Ying
Abstract : The abnormal neurites have long been regarded as the main player contributing to the poor outcome of patients with subarachnoid hemorrhage (SAH). (-)-Eigallocatechin-3-gallate (EGCG), the major biological component of tea catechin, exhibited strong neuroprotective effects against central nervous system diseases; however, the role of EGCG-mediated neurite outgrowth after SAH has not been delineated. Here, the effect of reactive oxygen species (ROS)/integrin β 1/FAK/p38 pathway on neurite outgrowth was investigated. As expected, oxyhemoglobin- (OxyHb-) induced excessive ROS level was significantly reduced by EGCG as well as antioxidant N-acetyl-l-cysteine (NAC). Consequently, the expression of integrin β 1 was significantly inhibited by EGCG and NAC. Meanwhile, EGCG significantly inhibited the overexpression of phosphorylated FAK and p38 to basal level after SAH. As a result, the abnormal neurites and cell injury were rescued by EGCG, which eventually increased energy generation and neurological score after SAH. These results suggested that EGCG promoted neurite outgrowth after SAH by inhibition of ROS/integrin β 1/FAK/p38 signaling pathway. Therefore, EGCG might be a new pharmacological agent that targets neurite outgrowth in SAH therapy.